2020
DOI: 10.1111/tpj.14872
|View full text |Cite
|
Sign up to set email alerts
|

PGRL1 overexpression in Phaeodactylum tricornutum inhibits growth and reduces apparent PSII activity

Abstract: Summary Proton gradient regulation 5‐like photosynthetic phenotype 1 (PGRL1)‐dependent cyclic electron transport around photosystem I (PSI) plays important roles in the response to different stresses, including high light. Although the function of PGRL1 in higher plants and green algae has been thoroughly investigated, little information is available on the molecular mechanism of PGRL1 in diatoms. We created PGRL1 overexpression and knockdown transformants of Phaeodactylum tricornutum, the diatom model species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Instead of forwarding electrons to FNR, Fd can also reduce components of AET routes to stimulate ATP synthesis under stress conditions. However, the exact mechanisms are not yet clear and contrasting views on the function of these AET complexes as alternative electron acceptors downstream of PSI have recently been brought forward (Nawrocki et al, 2019a; Buchert et al, 2020; Rantala et al, 2020; Zhou et al, 2020; Rühle et al, 2021; Wu et al, 2021). Nevertheless, it is well‐accepted that the energy balance is of high importance when it comes to altering metabolic processes (Kramer and Evans, 2010).…”
Section: Improving Crop Yields Through Optimization Of Photosynthetic...mentioning
confidence: 99%
“…Instead of forwarding electrons to FNR, Fd can also reduce components of AET routes to stimulate ATP synthesis under stress conditions. However, the exact mechanisms are not yet clear and contrasting views on the function of these AET complexes as alternative electron acceptors downstream of PSI have recently been brought forward (Nawrocki et al, 2019a; Buchert et al, 2020; Rantala et al, 2020; Zhou et al, 2020; Rühle et al, 2021; Wu et al, 2021). Nevertheless, it is well‐accepted that the energy balance is of high importance when it comes to altering metabolic processes (Kramer and Evans, 2010).…”
Section: Improving Crop Yields Through Optimization Of Photosynthetic...mentioning
confidence: 99%
“…It was suggested that the CET around PSI helps contribute electrons to synthesize ATP: Chlamydomonas ( Yadav et al, 2020 ), Phaeodactylum ( Zhou et al, 2020 ), C 3 ( Wang et al, 2015 ) and C 4 plants ( Munekage et al, 2010 ). There are at least two CET pathways in vascular plants and Phycophyta : antimycin A-sensitive pathway that involves proton gradient regulation 5 (PGR5) and PGR5-like photosynthetic phenotype 1 (PGRL1), and antimycin A-insensitive NADH dehydrogenase-like (NDH) pathway ( Figure 1A ; Munekage et al, 2002 ; Huang et al, 2005 ; Dalcorso et al, 2008 ; Taira et al, 2013 ; Ishikawa et al, 2016 ).…”
Section: Cyclic Electron Transportmentioning
confidence: 99%
“…In addition, high ΔpH not only decelerates the damage to PSII by protecting the OEC, but also protect PSI by regulating electron transport from PSII to PSI ( Takahashi et al., 2009 ; Tikkanen et al., 2015 ). Similarly, cyclic electron flow around PSI plays an essential role in photoprotection for P. henryi , C. cerasoides and Phaeodactylum tricornutum under high-light ( Huang et al., 2017 ; Yang et al., 2019b ; Zhou et al., 2020 ; Sun et al., 2021 ). ETRI - ETRII, NPQ, ETRI and ETRII were increased, P m was substantially reduced in the 29.8% FL plants ( Figures 3A , 4C , 6A ), and Y(NPQ), NPQ and Y(ND) have a positive correlation with ETRI - ETRII ( Figure 8 ), suggesting that cyclic electron flow around PSI protects PSI and PII from damage by enhancing thermal dissipation capacity and regulating P700 + redox state and electron transport in high-light-grown individuals.…”
Section: Discussionmentioning
confidence: 99%